Factors Associated With Adherence to Osteoporosis Medications Among Male Veterans. (30th June 2021) - Sagalla, Nicole; Lee, Richard; Sloane, Richard; Lyles, Kenneth; Colón‐Emeric, Cathleen
ABSTRACT: Risk factors for nonadherence to osteoporosis medication have been well described for cohorts of women with osteoporosis, but little is known about predictors or mediators of nonadherence in men. We conducted a secondary analysis of a national cohort of male veterans to explore factors associated with nonadherence to osteoporosis medications. We included veterans with a prescription for an oral bisphosphonate or calcitonin between 2000 and 2010. We identified demographic, comorbid, and fracture‐related risk factors by their International Classification of Diseases‐9 (ICD‐9) and Current Procedural Terminology (CPT) codes and used multivariable logistic regression to evaluate their association with adherence. Adherence was measured by medication possession ratio (MPR) over 5 years, starting at the time of their first prescription during the study period and censoring at death or end of study period. Of 135, 306 men identified with at least one prescription for an osteoporosis medication during the study period, 90, 406 (67%) were nonadherent (MPR < 0.80). The median duration of therapy was 3.2 years (interquartile range [IQR] = 1.7–5.0). In the fully adjusted model, the odds of adherence were lower in those aged <65 years (odds ratio [OR] = 0.87; 95% confidence interval [CI] 0.84–0.89), with no copay (OR = 0.78; 95% CI 0.76–0.80), dementia (OR = 0.87; 95% CI 0.83–0.91), anxiety/depression (OR = 0.92; 95% CI 0.90–0.95), tobacco use (OR = 0.91; 95% CI 0.89–0.94), alcohol abuse (OR = 0.91; 95% CI 0.89–0.94), rheumatoid arthritis (OR = 0.92; 95% CI 0.87–0.97), and on androgen deprivation therapy (OR = 0.89; 95% CI 0.83–0.95). The odds of adherence were higher in whites (OR = 1.14; 95% CI 1.11–1.17), with a prior screening colonoscopy (OR = 1.12; 95% CI 1.09–1.14), on alendronate versus other agents (OR = 1.61; 95% CI 1.55–1.67), with a dual‐energy X‐ray absorptiometry (DXA) (OR = 1.14; 95% CI 1.12–1.17), on glucocorticoids (OR = 1.08; 95% CI 1.02–1.14), and with recent fracture (OR = 1.07; 95% CI 1.04–1.10). In conclusion, adherence to oral bisphosphonates/calcitonin is poor, with particular subgroups at greatest risk. These findings may help tailor approaches for supporting adherence in men prescribed osteoporosis medications. © 2021 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.